Innovative online learning strategies for the successful construction of student self-awareness during the COVID-19 pandemic: Merging TAM with TPB - Yuna Yao; Ping Wang; YuJun Jiang; Qiang Li; Yingji Li (Journal of Innovation & Knowledge, 2022)
The ongoing Corona Virus Disease 2019 (COVID-19) pandemic presents several challenges to the education system including technical, cognitive, managerial, and behavioral ones. As a result of these pressures, education systems are undergoing dramatic changes. The persistent state of the pandemic leading to anincrease in connectivity between teachers and students' devices, and the growth of online learning, is changing how students learn and the risks they have to manage themselves. The education sector typically employs some technical models to assess students' attitudes. Moreover, there is an ongoing intention to use online learning. In addition to technological factors, psychological factors were incorporated into the assessment. And intentions and attitudes are from a cognitive standpoint. Based on empirical research on online learning conducted among university students under epidemic normalization, the main goal of this paper is to examine the relationship between self-awareness and the willingness to use it continuously. During COVID-19 pandemic, the research framework created for this study was tested on 429 college students. The integrated Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB) model's hypotheses were empirically examined. It was found that self-awareness and the intention to use online learning during the epidemic are consistently related. Self-awareness profoundly and significantly impacts the decision to continue using online learning. The study's findings can gauge participants' intent to continue. This study's result can help assess the intention to continue to use online learning during COVID-19.This can help provide more valid assessment results beneficial for the management of online learning.